تحسين أداء لقمة المكبح المستخدمة في نظام الفرملة للقطار (Latakia University Journal -Engineering Sciences Series, 2016)
يتضمن هذا البحث دراسة لتحسين أداء لقم الكبح المستخدمة في السكك الحديدية، حيث يعتمد هذا البحث على المعالجة الحرارية للقم الكبح المصنوعة من حديد الصب الرمادي، مما يسمح بالحصول على بنية بلورية جديدة لحديد الصب تعطيه قساوة عالية ومقاومة اهتراء عالية، كما أنه يضاعف من عمرها الفني ويزيد من عامل السلامة والأمان على شبكة السكك الحديدية. وقد تمت مقارنة نتائج الاختبارات للعينات المعالجة حراريا مع العينات التي لم تخضع لمعالجة حرارية، وأعطت عمليات المعالجة نتائج جيدة تسمح بتطبيق هذه العمليات على اللقم المستخدمة حالياً على شبكة الخطوط الحديدية السورية . This study includes a work to improve the performance of brake shoe which is used in rail, where it depends on heat treatment to brake shoe which is made ​​of gray cast iron, which makes the occurrence of the largest dissolve of the carbon in austenite. It allows obtaining a new crystalline structure of cast iron which has high toughness and high wear resistance. It increases the life service of brake shoe, and increases safety factor on rail way.   The test results were compared to the heat treated samples with samples that were not subjected to heat treatment, and treatment processes gave good results that allow to apply these operations on bits currently used on the railway network in Syria.